PERKEBUNAN SAWIT RAKYAT DI DESA PULAU KERAKAP - Naufal Brillian Harryunanda, Rafiffadhil; Heidi Karmela, Siti; Yanto, Ferry (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2024)
This research is a type of historical research with the theme of economic history, especially at the microeconomic level about smallholder oil palm plantations in Pulau Kerakap Village. The goal is to describe the growth and development of the smallholder oil palm plantation sector in Pulau Kerakap Village which is an important economic sector for the population, especially for economic actors involved in these economic activities. Furthermore, it also aims to explain the economic life of residents in Pulau Kerakap Village starting from those who become farmers as well as owners, laborers, and middlemen as a result of the growing oil palm plantation sector. For research methods is the historical method, which has stages of research ranging from heuristics, criticism, interpretation, and historiography aimed at achieving historical truth. This research is also complemented by the use of a theoretical approach that is multidisciplinary by applying other social science concepts such as economics. The findings in the field show that smallholder oil palm plantations in Pulau Kerakap Village are an important economic sector for the population, especially for farmers who own oil palm plantations, laborers, middlemen, and oil palm processing companies. Inhabited by residents ranging from indigenous people (Jambi Malays) to local and general transmigrants. The condition of the smallholder oil palm plantation sector shows fluctuating conditions, one of which is the fluctuation in the nominal amount of workers' wages.